Design and implementation DVB-S & DVB-S2 systems - Samir Jasim Mohammed; Zaid Saadi Hussein (Institute of Advanced Engineering and Science, 2020)
Digital video broadcasting plays an important role in most digital communication systems. Digital broadcasting systems are designed with great accuracy and delicate design which has a major role in our lives today especially digital video broadcasting. It is these systems that are considered to be the most advanced in transmission, reception and reliability. From these systems they develop through the digital video broadcasting project group.The most important are digital video broadcasting of terrestrial, digital video broadcasting of cable and digital video broadcasting of satellite because of that many user's desires to use communications and entertainment in their lives there are new and demanding situations that the standards of these systems can only meet for their own applications .In this paper, it will design and implement the digital video broadcasting of satellite first generation and digital video broadcasting of satellite second generation of binary data,image and audio using Matlab-Simulink environment.In addition, will calculate the bit error rate of the signal. This system is designed with precision to improve performance errors and increase transmission capacity as well as provide a safe environment for information.